Reliable person in the net of the KGB in the Lithuanian SSR - Okuličiūtė, Lina (Genocidas ir rezistencija, 2007)
Nowadays, the sensitive issue to Lithuanian society of secret agents of the former Soviet repressive institution the KGB (Committee for State Security) is being raised more and more often. In order to use agents more effectively and productively, a reorganization of the KGB was performed in 1952. The category of a liquidated informant (a person supplying information) was substituted by a new one, the category of reliable person. A reliable person was a Soviet citizen who at the request of the KGB reported on individuals and facts which were worth operational attention, and who did particular tasks. Reliable persons were chosen from so-called Soviet patriots on a voluntary principle. Operational contact was established with people who seemed interesting to the KGB to deal with intelligence or counter-intelligence tasks. These reliable people, doing permanently various tasks ordered by the KGB, were eventually recruited as agents. Instead of a not very useful agency, which could be used for watching different individuals, reliable people were used. In the 1950s and 1960s, the KGB in the Lithuanian SSR still had a lot of useless, unemployed agents, most of whom were only used for searches of suspected people. It appeared that reliable people could do the same work. This is the reason why it was decided to use reliable individuals rather than recruiting low-value agents. These spies worked out of ideological conviction, often not hiding their pro-Soviet attitude.
Keywords: KGB; agents; reliable people